2013
DOI: 10.1002/ar.22790
|View full text |Cite
|
Sign up to set email alerts
|

Segmentation features and structural organization of the intrapulmonary artery of the yak

Abstract: This study aims to systematically investigate intrapulmonary artery segmentation, blood vessel wall characteristics and structure organization, and the interrelation between intrapulmonary artery structure and plateau hypoxia adaptation in yak. The normal intrapulmonary artery structure of the yak had been studied using histological methods and transmission electron microscopy. The intrapulmonary artery of the yak was also examined using morphometric analysis and angiography. Results showed that the elastic in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 36 publications
(42 reference statements)
0
8
0
Order By: Relevance
“…Heath et al has proved that there is no Pulmonary hypertension in yak [ 25 ]. Zhou et al reported that there were infact smooth muscle cells presented in the intrapulmonary arteriole of lung in yak, and the low oxygen environment can cause the thickening of the tunicae media of pulmonary artery of yak [ 26 ]. Researchers also found that the pulmonary artery of adult yak had more elastic fibers than that of adult cattle, which could maintain good retraction force of the pulmonary artery and ejecting blood [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Heath et al has proved that there is no Pulmonary hypertension in yak [ 25 ]. Zhou et al reported that there were infact smooth muscle cells presented in the intrapulmonary arteriole of lung in yak, and the low oxygen environment can cause the thickening of the tunicae media of pulmonary artery of yak [ 26 ]. Researchers also found that the pulmonary artery of adult yak had more elastic fibers than that of adult cattle, which could maintain good retraction force of the pulmonary artery and ejecting blood [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The heart and lungs are important organs involved in the adaptation to low temperature and hypoxic environments. Previous studies highlighted these organs in yaks due to their special morphological and physiological characteristics contributing to their adaptation to high‐altitude environments (Duan et al, 2012; Zhou et al, 2013). Compared to low‐altitude cattle, the lung of yak displays shorter and thicker trachea, and more alveoli and capillaries per unit area (Chen et al, 2006; Yang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The myocardium level of HIF-1α was higher in 2-year old yaks, than in younger and older ones. However, the myocardium HIF-dependent VEGF level increased throughout the animals' life and the oldest yaks demonstrated the highest levels (Duan et al, 2012;Zhou et al, 2013;He et al, 2016).…”
Section: Introductionmentioning
confidence: 97%